Soybean Oil and Beef Tallow in Starter Broiler Diets - Fascina, V B; Carrijo, A S; Souza, K M R; Garcia, A M L; Kiefer, C; Sartori, José Roberto [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2009)
The objective of this study was to determine the energy values of soybean oil (SBO) and tallow (T) combined in different ratios, and to evaluate their effects on the performance, body composition, and serum lipid levels of starter broilers. In experiment I, a digestibility trial was performed to determine the energy value of the SOB and T mixtures using 100 12 - to 21 -day-old broilers. In experiment II, 930 one-day-old broilers were used. Treatments consisted of the inclusion of 4% SBO and T inclusions at the following ratios: 0:100, 25:75, 50:50, 75:25, 100:0. Each treatment included six replicates. In experiment I, AME and AMEn linearly increased (P<0.01), as SBO participation in the mixture increased. In experiment II, the different lipid ratios quadratically influenced (P<0.01) body weight and weight gain at 21 days of age, increasing up to the ratio of 65.87:34.13. Serum lipids linearly decreased (P<0.05) as SOB inclusion in the diet increased. It was concluded that AME and AMEn of SBO and T at ratios of 0:100, 25:75, 50:50, 75:25, and 100:0 were 7.882 and 7.542, 8.384 and 8.076, 8.701 and 8.385, 8.801 and 8.727, and 9.478 and 9.271 kcal/kg, respectively. The best performance with no detrimental effect on carcass yield was obtained with the mixture of 75% SBO with 25% T. The highest dietary soybean oil level reduced serum lipid levels of 21-day-old broilers.
Keywords: Fats; energy value; oils; performance; serum lipids